Алелопатичні особливості інтродукованих видів роду Tagetes L. - Maschkovska, S.P. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2000)
Allelopathic activity of three species of the Tagetes (Tagetes erecta L., T. patula L., T. signata Bartl.) has been studied with respect fo incement of roots and coleoptiles of the winter wheet. We have determined that water extracts and volatile secretions of leaves and floscules of Tagetes signata are characterized by the greatest phytotoxicity.